The arts in early England - Brown, G. Baldwin (J. Murray, 1903)
v. 1. The life of Saxon England in its relation to the arts.--v. 2. Ecclesiastical architecture in England from the conversion of the Saxons to the Norman conquest. Appendix: Index list and map of Saxon churches.--v. 3-4. Saxon art and industry in the pagan period.--v. 5. The Ruthwell and Bewcastle crosses, the Gospels of Lindisfarne, and other Christian monuments of Northumbria; with philological chapters by A. Blyth Webster.--v. 6, pt. 1. Completion of the study of the monuments of the great period of the art of Anglian Northumbrie.--v. 6, pt. 2 Anglo-Saxon sculpture, prepared for press by E.H.L. Sexton.